Implications Of Marriage Dispensation In Increasing Divorce Filings - Vica Zumrotun Nisa; Isdian Anggraeny (Publikasi Indonesia, 2023)
In principle, the limit on the age of marriage for citizens is to ensure that couples about to marry must have sufficient mental and physical maturity. The minimum age limit for marriage has been regulated by legal provisions and compilations of Islamic law, but there are still differences in determining the age limit. The Amended Marriage Law Number 16 of 2019 has stipulated that the minimum age for marriage for women is the same as for men, namely 19 (nineteen). The ratification of this provision must be a response to public unrest. This can happen because perpetrators of child marriage often lack mental and even economic preparation for a household, causing protracted conflicts. In writing this law, the author wants to examine the factors that cause underage marriages and the influence of underage marriages on the divorce rate in Mojokerto Regency to know the causes of underage marriages, underage marriages, and the impact of underage marriages against divorce. This study uses standard experimental research methods, and the data obtained will be analyzed using a qualitative descriptive method. The results of this study show that in Mojokerto Regency, early marriage is due to parental pressure, economic factors, and pregnancies outside of marriage. As a result, conflicts that cannot be sustained in these marriages often arise and end in divorce